Students’ Perceptions Towards The Use of Google Classroom in Supporting Grammar Understanding - Leanna Apsari Aristawati; Khoirul Anwar; Ulfatul Mari'fah (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates students’ perceptions towards the use of Google Classroom in supporting grammar understanding. While previous research has explored the use of Google Classroom in developing language skills such as speaking, writing, and listening, limited attention has been given to its role in enhancing grammar comprehension. Addressing this gap, the present research aims to explore how students perceive the effectiveness of Google Classroom in learning grammar, and to identify challenges encountered during its use.A sequential explanatory mixed-method design was employed, beginning with the collection and analysis of quantitative data, followed by qualitative data to provide deeper insights. The participants were selected from a group of English language learners who had experience using Google Classroom as part of their grammar instruction. Data collection tools included questionnaires for the quantitative phase and interviews for the qualitative phase.The findings reveal that students generally have positive perceptions of using Google Classroom to support grammar understanding. The data show that 54.3% of participants agreed that the platform contributes to improved grammar comprehension, while 51.4% viewed it as effective in facilitating grammar-related tasks. Despite the overall positive response, students reported several challenges, including the lack of automatic updates, which required manual page refreshes, and technical difficulties related to internet connectivity and device compatibility.These findings suggest that Google Classroom holds potential as a supportive tool in grammar instruction, though technical improvements and additional guidance may be needed to optimize its effectiveness. The results contribute to the growing body of research on digital learning environments and their impact on language acquisition, particularly in the context of grammar learning.